عنايةُ الإمَام النَّفَراوي بالمصَادر الاستدلاليّة في كتَابه الفَواكه الدَّوَانِي على رسالة ابن أبي زيد القيرواني (Journal of Humanitarian and Applied Sciences, 2023)
This research dealt with the study of a book from the books of Maliki jurisprudence, which is Al-Fawakhat Al-Dawani on the message of Ibn Abi Zaid Al-Qayrawani to the great scholar Ahmed Al-Nafrawi. Ibn Abi Zaid al-Qayrawani in his letter. In this study, I followed the analytical inductive approach, and divided the research into an introduction, a preface, and two demands. The research, the research plan, and as for the preface, I dealt with the definition of the author and the definition of the book, and it came in the first requirement:The inferences of Imam al-Nafrawi in the Holy Qur’an in the chapter on prayer and the chapter on zakat, and the second requirement: the inferences of Imam al-Nafrawi in the Holy Qur’an in the chapter on marriage and waiting period and in the chapter on blood and borders, and at the end of the research there is a conclusion: it contains the most important results drawn from the folds of this study.
Keywords: Evidence; judgments; reasoning; Al-Nafrawi; legitimacy